2017
DOI: 10.1007/s13665-017-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Ultrasound: What Non-radiologists Need to Know

Abstract: Purpose of reviewThe aim of this review is to provide the theoretical and practical knowledge essential for non-radiologists to develop the skills necessary to apply thoracic ultrasound as an extension of clinical assessment and intervention.Recent findingsIssues relating to training and competence are discussed and a library of thoracic ultrasound videos is provided to illustrate artefacts, pleural, parenchymal and pneumothorax pathology as well as important pitfalls to consider. Novel and future diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The ability of LUS to detect pleural effusion with high specificity is already known . In our experience, the qualitative aspect of the effusion could also be assessed and, in some cases, could differentiate between transudate, exudate and empyema (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…The ability of LUS to detect pleural effusion with high specificity is already known . In our experience, the qualitative aspect of the effusion could also be assessed and, in some cases, could differentiate between transudate, exudate and empyema (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…The evaluation of pleural gliding signs needs a duration of ventilation and working knowledge of the operators. [ 12 , 13 , 20 ] When LDLTs were used, the evaluation time of the FR was significantly shorter than the AR and UR. The evaluation time for ultrasound in the present study was shorter than that reported by Ramsingh, which was 162 ± 38 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous experiments, [ 4 , 20 , 21 ] the hypothesis of this study was that there would be a 20% difference between auscultation and ultrasound in terms of the accuracy of the evaluation of the DLT position. In order to detect this difference with a power of 80% and a P -value of .05, the power calculation indicated that a sample size of at least 35 experimental subjects and 35 control subjects is needed to reject the null hypothesis, in which the failure rates for the experimental and control subjects are equal, with a probability (power) of .8 and a type I error of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…17 Moreover, the diagnosis of pneumothorax should be combined with the lung point, barcode sign on M mode and absence of lung sliding. 13,[18][19][20] On this basis, the absence of pleural sliding in the anterior, lateral or posterior chest on LUS was de ned as small, medium or large pneumothorax. 21 The presence of anechoic area uctuating with respiration indicated pleural effusion.…”
Section: Lung Ultrasound Examinationmentioning
confidence: 99%